Labor market adjustments after a large import shock: evidence from the German clothing industry and the multi-fibre arrangement - Nils Braakmann; Joachim Wagner (Institute for the Study of Labor (IZA), 2009)
This paper considers labor market adjustments following a large import shock in the German clothing industry caused by the phasing out of the Multi-Fibre Arrangement. Using the German shoe industry as a control group and administrative data, we study adjustments on the individual and firm level using difference-in-differences. Our results suggest relatively small increases in unemployment risk and no wage effects on the individual level, despite a 30% increase in plant mortality. Part of the different effects found for plants and individuals can be attributed to the reallocation of workers into other industries and occupations.
Keywords: F13; F14; F16; 330; Import shock; adjustment; clothing industry; Germany; Bekleidungsindustrie; Schuhindustrie; Schock; Beschäftigungseffekt; Schuhe; Import; Arbeitsmobilität; Allokation; Deutschland; Welttextilabkommen; Außenhandelsliberalisierung; Welt